Cooperation behaviour of road users in t-intersections during deadlock situations. (October 2018) - Imbsweiler, Jonas; Ruesch, Maureen; Weinreuter, Hannes; Puente León, Fernando; Deml, Barbara
Highlights: Experimental study for a cooperative t-intersection deadlock scenario. Testing of different approaching behaviours for designing automated vehicles. In complex situations, drivers prefer to let their cooperation partners drive first. Explicit Communication signals tend to be given more to the right than to the left. Abstract: Mixed traffic between automatic guided cars and human road users makes it necessary to understand cooperative behaviour between road users in order to adapt automated behaviour to human expectations. Road traffic offers various challenges, one being cooperative situations, which are not regulated by law. For example a t-intersection in which one road user is driving straight forward and two road users are turning left. To solve this situation the road users have to cooperate with each other. Different kinds of approaching behaviours in such situations were generated and analyzed according to cooperation readiness, preference to drive first and perceived safety of the situation by means of an experiment. The results show that in complex situations – like the investigated scenario – human road users prefer not to drive first. Additionally a high cooperation readiness of the opposite driver combined with a defensive driving style received higher ratings in the "confidence of passing".